POSITIONING THE MEANING OF WASATIYYAH IN RELIGIOUS MODERATION - Suharto, Ahmad; Sadili, Ridwan; Maulana, Abdullah Muslich Rizal; Mustikasari, Intan Pratiwi (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2023)
This study discusses the concept of wasa?iyyah concerning religious moderation campaigned by the Indonesian government. This study is critical because several studies state that the two have similar meanings. Still, each has distinct identities and characteristics that need to be discussed academically as further consideration of the concepts presented. Wasa?iyyah is a middle way of thinking and acting in Islam, not merely referring to a standing position between the two, but is associated with the best and foremost balance. This study uses discourse analysis to understand the conceptual definition of both wasatiyyah and moderation. This study concludes that the meaning of Wassatiyah contains several different elements, whereas Wasatiyyah is mainly built on theological constructions based on the Al-Qur'an. Wasa?iyyah, on the other hand, is an offer made from an Islamic point of view to engage in efforts to deradicalize religion with several characteristics and traits found in the Qur'an and formulated by Islamic scholars.